Far-field superoscillatory metamaterial superlens - Yuan, Guanghui (2019)
We demonstrate a metamaterial superlens: a planar array of discrete subwavelength metamolecules with individual scattering characteristics tailored to vary spatially to create subdiffraction superoscillatory focus of, in principle, arbitrary shape and size. Metamaterial free-space lenses with previously unattainable effective numerical apertures – as high as 1.52 – and foci as small as 0.33λ in size are demonstrated. Super-resolution imaging with such lenses is experimentally verified breaking the conventional diffraction limit of resolution and exhibiting resolution close to the size of the focus. Our approach will enable far-field label-free super-resolution nonalgorithmic microscopies at harmless levels of intensity, including imaging inside cells, nanostructures, and silicon chips, without impregnating them with fluorescent materials.